Orientation dependent glacial changes at the Tibetan Plateau derived from 2003–2009 ICESat laser altimetry ... : التغيرات الجليدية المعتمدة على الاتجاه في هضبة التبت المستمدة من قياس الارتفاع بالليزر ICESat 2003–2009 ... - Vu Hien Phan; Roderik Lindenbergh; Massimo Menenti (OpenAlex, 2014)
Abstract. Monitoring glacier changes is essential for estimating the water mass balance of the Tibetan Plateau. Recent research indicated that glaciers at individual regions on the Tibetan Plateau and surroundings are shrinking and thinning during the last decades. Studies considering large regions often ignored however impact of locally varying weather conditions and terrain characteristics on glacial evolution, due to orographic precipitation and variation in solar radiation. Our hypothesis is therefore that adjacent glaciers of opposite orientation change in a different way. In this study, we exploit ICESat laser altimetry data in combination with the SRTM DEM and the GLIMS glacier mask to estimate glacial vertical change trends between 2003 and 2009 on the whole Tibetan Plateau. Considering acquisition conditions of ICESat measurements and terrain surface characteristics, annual glacial elevation trends were estimated for 15 different settings. In the final setting, we only include ICESat elevations ... : الملخص. تعد مراقبة التغيرات في الأنهار الجليدية أمرًا ضروريًا لتقدير توازن الكتلة المائية لهضبة التبت. أشارت الأبحاث الحديثة إلى أن الأنهار الجليدية في المناطق الفردية على هضبة التبت والمناطق المحيطة بها تتقلص وتضعف خلال العقود الماضية. غالبًا ما تتجاهل الدراسات التي تنظر في المناطق الكبيرة تأثير الظروف الجوية المتغيرة محليًا وخصائص التضاريس على التطور الجليدي، بسبب هطول الأمطار الجليدي والتباين في الإشعاع الشمسي. لذلك فإن فرضيتنا هي أن الأنهار الجليدية المجاورة ذات الاتجاه المعاكس تتغير بطريقة مختلفة. في هذه الدراسة، نستغل بيانات قياس الارتفاع بالليزر ICESat جنبًا إلى جنب مع SRTM DEM وقناع الأنهار الجليدية GLIMS لتقدير اتجاهات التغيير الرأسي الجليدي بين عامي 2003 و 2009 على هضبة التبت بأكملها. بالنظر إلى ظروف الحصول على قياسات ICESat وخصائص سطح التضاريس، تم تقدير اتجاهات الارتفاع الجليدي السنوية لـ 15 بيئة مختلفة. في الإعداد النهائي، نقوم فقط بتضمين ارتفاعات ICESat المكتسبة على التضاريس التي يقل ميلها عن 20درجة وخشونة عند مقياس البصمة أقل من 15 مترًا. ضمن هذا الإطار، يمكن تمييز 90 منطقة جليدية. تظهر النتائج ...